Reação de acessos de meloeiro a Myrothecium roridum e herança da resistência a podridão-de-cratera - Nascimento, Itala Jane Bezerra do (2008)
Many problems occur in melon farming, among them, the rot-of-crater, caused by the fungus Myrothecium roridum. The genetic resistance is one of the alternatives of control that combined with other practices can reduce the effect of this disease. To achieve cultivars with resistance is necessary to identify the sources of resistance and obtain information on the genetic control of resistance. The objectives of the present work were to evaluate the reaction of melon germplasms and study the heritage of resistance to rot-of-crater. In the first experiment, were assessed 30 accessions of melon collected in northeastern Brazil. The experimental design was randomized blocks with two repetitions. The plot was formed by a line with twelve plants. From each plot was taken a sample of three fruits for inoculation. Each fruit was inoculated in four equidistant points on the surface. In each point was observed a total of 10 injuries of about 3.0 mm in depth. The deposition of 0.05 mL of the suspension of conidia in concentration of 106 spore mL-1 of distilled water was done by injection subepidermal immediately after the injury to the fruit. The fruits were put on petri dishes and wrapped up in polyethylene bag, containing hydrophil cotton wetted with sterile distilled water, providing a wet camera. The assessment was made five days after inoculation through a scale of notes, observing the symptoms in the fruits. The accessions A-9, A-14 and A-30 were those who stood out as resistant to isolate LE-609 of M. roridum. In the second experiment, the parents F-682 and UFRPE-05 were used as patterns of susceptibility and resistance, respectively. The following generations F1, F2, RC11 and RC12 were obtained from the same parents. The obtained six populations were grown in field conditions in randomized blocks. The heritage of resistance to rotof- crater in melon fruits to isolate LE-609 had heritage complex, with nine loci and involvement of additive effects and dominance